Depression and depressive disorder: a study using DSM 111-R criteria. - Perera, A (My University, 1992)
The objectives were, to estimate the prevalence of depressive phenomena, to identify demographic risk factors, observe phenomenology and assess severity.The prevalence rate of depressive disorder was 7.7 per cent. Elderliness (55 year), female sex,widowhood, low education ,being a housewife, low occupation in the male and economic unproductivity emerged ad significant risk factors. Subtyping by DSM-III-R criteria showed that moderate major depressive episode was the commonest and major depressive episode with psyctatic features the least common.Fain and dyspepsia were the most common presenting symptome and multiple symptoms, as well as multiple organ inclvement were characeristic feature of the depressive studies.While affictive and vegetative symptom were typical,cognitive symptoms of depression were infrequent.Hypochondriasis and anexity too,were very common. Seveity essessment by subtyping showed that 60 per cent to be moderately or severely depressed, 66 per cent of the depressives were found to be incapacitated functionally to a moderate degree at least by globle assessment of functioning scale criteria.By hamilton depression scale criteria 53 per cent were severly depressed, while 40 per cent were moderately and 7 per cent mildly depressed.The respective beck depression inventory figures were 26 per cent ,32 per cent and 42 per cent validity and reliability of the findings,limitation and implication of the conclusion are discussed.